Self-growth of graphene nanosheets on a crystalline nanodiamond substrate using NixZnxO catalyst and their efficient photodetection properties. (September 2020) - Kathiravan, Deepa; Huang, Bohr-Ran
Highlights: Graphene nanosheets are self-grown on nanodiamond using Nix Znx O catalyst. In this novel strategy, 1D nanostructure is transformed to 2D nanostructured material. The present nanocomposite shows good broadband spectral range from 200 to 800 nm. Also, the presented hybrid device shows an enhanced on/off current ratio ( 6037) and responsivity of 3 mA/W. Abstract: The correlation of structure-properties in material chemistry has stimulated the synthesis of innovative materials with unique nanostructures. At the same time, these new kinds of nanostructures can be fascinating building blocks for future photodetection platforms. Here, we report on the self-growth of fine-edged graphene oxide sheets on crystalline nanodiamond (CND) substrates using Nix Znx O as a catalyst and a simple soft chemical method. In this novel strategy, one-dimensional (1D) Nix Znx O nanostructures are converted into two-dimensional (2D) nanostructures, with the self-growth of graphene on a CND substrate, as evidenced from Raman, XRD and TEM measurements. It is envisioned that these self-assembled 2D graphene sheets on Nix Znx O/CND will promote the performances of broadband spectrum Nix Znx O photodetectors. Then, Ag electrodes is used to fabricate the present hybrid nanostructure (graphene/ Nix Znx O nanopellets/CND substrate) and utilized for photodetection studies. The as-fabricated hybrid structure exhibited remarkable photo-detection properties compared to those of pristine Nix Znx O and ZnO/CND based photodetectors. Specifically, the presented hybrid device shows an enhanced on/off current ratio ( 6037), a rapid response/recovery speed (39/32 s), and decent photoresponsivity (3 mA/W), which are superior to those reported to date for crystalline nanodiamond based photodetector studies. In addition, the synergistic effects between graphene and Nix Znx O/CND greatly improve the broad range absorption. The enhanced photodetection properties of this hybrid device can be ascribed to the formation of multiple depletion regions and intermediate energy levels. It is hoped that these results will inspire the design and fabrication of innovative nanostructures for high-performance optoelectronic applications. Graphical abstract: Image, graphical abstract